Weekly Drinking and Binge Drinking Mediate the Association Between Drinking Location and Sexual Coercion - Ehlke, Sarah J. (Journal of interpersonal violence, 2021)
It has been well documented that alcohol use is a risk factor for sexual assault. However, few studies have examined how alcohol use is associated with sexual coercion experiences. Furthermore, off-campus parties and bars are drinking locations where alcohol use is high among college students. It is important to determine other risk factors, such as the drinking location, that may affect alcohol use and sexual coercion. The current study examined whether alcohol use (drinks per week and binge drinking) mediated the association between drinking location frequency (off-campus party and bar/restaurant) and experiencing sexual coercion in the past 30 days. Participants were N = 295 young adult (Mage = 21.17 years, SD = 2.70) undergraduate women who reported drinking at least once in the past 30 days and completed an online survey. Results revealed that 88 (29.8%) participants experienced sexual coercion in the past 30 days. Participants who experienced sexual coercion in the past 30 days reported greater drinks per week, were more likely to binge drink, and reported drinking more frequently at off-campus parties than those who had not experienced sexual coercion. Drinks per week significantly mediated the relationship between drinking location frequency (off-campus party and bar/restaurant) and sexual coercion. Specifically, more frequent drinking at off-campus parties and bars/restaurants was associated with greater drinks per week, which in turn was related to experiencing sexual coercion in the past 30 days. Binge drinking significantly mediated the association between frequency of drinking at a bar/restaurant and sexual coercion, but not off-campus drinking frequency. Findings suggest that college student alcohol interventions that target harm reduction should consider including information about how the drinking location may intersect with alcohol use to increase risk for sexual coercion.